Effect of high-pressure pretreatment on enzymatic hydrolysis of a mixture of rainbow trout (Oncorhynchus mykiss) and Atlantic salmon (Salmo salar) rest raw material - Kotsoni, Elissavet; Daukšas, Egidijus; Aas, Grete Hansen; Rustad, Turid; Tiwari, Brijesh; Cropotova, Janna (Frontiers in Sustainable Food Systems, 2024)
Introduction Fish rest raw material generated from the fish processing industry may be a useful resource for recovery of added value compounds. The application of non-thermal novel technologies can improve the extraction. High-pressure processing (HPP) has long been used for the preservation and extension of the shelf life of seafood. It also constitutes a promising technology for the increased recovery of valuable compounds, such as lipids and proteins. The objective of this study was to assess the yield and the chemical composition of the fractions obtained after enzymatic hydrolysis on a mixture of Atlantic salmon (Salmo salar) and rainbow trout (Oncorhynchus mykiss) rest raw material pretreated by high-pressure (HP). Methods Six different pretreatments were applied prior to enzymatic hydrolysis; 600 MPa x 8 min, 600 MPa x 4 min, 400 MPa x 8 min, 400 MPa x 4 min, 200 MPa x 8 min, 200 MPa x 4 min. Results and discusssion These applied pretreatments did not yield higher oil extraction compared to the control. However, the fish protein hydrolysates (FPH) contained higher amount of protein when compared to the FPH obtained from the control.